The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym12102231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PMMA/Silica Hybrid Particles on Interfacial Adhesion and Crystallization Properties of Poly(lactic acid)/Block Acrylic Elastomer Composites

Abstract: Poly(lactic acid) (PLA) is a relatively brittle polymer, and its low melt strength, ductility, and thermal stability limit its use in various industrial applications. This study aimed to investigate the effect of poly(methyl methacrylate) (PMMA) and PMMA/silica hybrid particles on the mechanical properties, interfacial adhesion, and crystallization behavior of PLA/block acrylic elastomer. PLA/block acrylic elastomer blends exhibit improved flexibility; however, phase separation occurs between PLA and block acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The silica, as an additive, is used in coatings, food, and biomedical applications. For example, silica as a bio-safe additive can be incorporated along with silver nanoparticles to improve the antibacterial properties and corrosion properties of biomaterials [13][14][15][16][17][18][19][20][21][22][23]. The amorphous silica nanoparticles extracted from natural sources, such as rice husk and fly ash, can be used as a nucleating agent when added to thermoplastic polymers in very low amounts, owing to their large surface area [24].…”
Section: Introductionmentioning
confidence: 99%
“…The silica, as an additive, is used in coatings, food, and biomedical applications. For example, silica as a bio-safe additive can be incorporated along with silver nanoparticles to improve the antibacterial properties and corrosion properties of biomaterials [13][14][15][16][17][18][19][20][21][22][23]. The amorphous silica nanoparticles extracted from natural sources, such as rice husk and fly ash, can be used as a nucleating agent when added to thermoplastic polymers in very low amounts, owing to their large surface area [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the drawbacks of pure PLA, the addition of fillers in its matrix is preferred [11,12]. Lack of thermal and mechanical stability is one of the main drawbacks of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers 2020, 12, x FOR PEER REVIEW 3 of 20 been reported that silica disperses well in PLA and results in improved mechanical and thermal properties, and also enhances the crystallinity of the structures [30][31][32]. Moreover, since silica is reported to have high silanol groups, siloxane bridges, and hydroxyl groups [12], it can be easily functionalized, opening pathways for several applications such as biomedical, separation, catalysis, and sensors [17,33]. Figure 2 represents different types of silanol groups and siloxane bridges on the silica surface and its internal OH groups [34].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing additives into polymer matrix is an important method for improving the performances of polymers or even developing new functionalities [1]. In terms of Poly(L-lactide) (PLLA), although PLLA presents some advantages such as high transparency [2], excellent degradability and biocompatibility [3,4], high modulus [5], and easy processability [6], PLLA also suffers from several serious defects including slow crystallization rate, low crystallinity, poor heat resistance and low melt strength [7,8], for this reason, the overall usage of PLLA by plastic manufacturers is hindered. Slow crystallization is regarded as one of the most serious defect in the present situation, because, on one hand, crystallization rate is directly related to the injection molding cycle which affects manufacturing cost of PLLA-based products; on the other hand, the resulting PLLA-based product's heat resistance and mechanical properties sorely depend on crystallinity determined by the crystallization rate.…”
Section: Introductionmentioning
confidence: 99%